THE IMPORTANCE OF PROVIDING LANGUAGE COMMUNICATION MATERIAL IN ADVANCED ENGLISH COURSE - Hayrapetyan, Naira (Foreign Languages for Special Purposes, 2025)
When organizing an advanced English language course, it is necessary to select and teach language material from new methodological perspectives. The development of socio-cultural awareness is a prerequisite for mastering language material. In other words, communicative awareness is based not on linguistic, but on socio-cultural and pragmatic awareness. From the perspective of advanced English learning, it is important that learners master the language as a means of communication. In the new methodical system, the role of grammatical knowledge is not underestimated, but the development of communication abilities and skills remains the priority. The main goal of advanced English learning is not grammatical rules, but effective assimilation of speech patterns.